El origen de la argolla peruana y la evolución de un discurso sobre la exclusión social - Nureña, César R. (Notas de Antropología de las Américas, 2023)
In Peru, the term argolla went from being just a way to designate an elite segment in the 19th century, to concentrate nowadays a vast range of meanings, referring to closed groups in any field, but also types of relationships, attitudes, behaviors, problems, cultures and even native theories on the abuse of power. This article examines how this proliferation of meanings occurred, in relation to certain sociopolitical changes in Spain and America in the 17th to 20th centuries.